2017
DOI: 10.1177/0954409717720838
|View full text |Cite
|
Sign up to set email alerts
|

Suggestion for allowable additional compressive stress based on track conditions

Abstract: A continuous welded rail has immovable zones due to its structural characteristics. In an immovable zone, thermal expansion and contraction of rails are restricted when the temperature changes, thereby causing excessive axial force on the rail. When the immovable zone of the continuous welded rail is located on a bridge, additional stress and displacement occur through track–bridge interactions. Additional stress and displacement of the rail compared to the embankment area are restricted when constructing the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 6 publications
(12 reference statements)
0
5
0
Order By: Relevance
“…The FE model for the CWR track on the bridge is constructed based on the modeling approach of previous research [13]. The model consists of bridge and embankment regions, as shown in Figure 7.…”
Section: Modeling Methodsmentioning
confidence: 99%
“…The FE model for the CWR track on the bridge is constructed based on the modeling approach of previous research [13]. The model consists of bridge and embankment regions, as shown in Figure 7.…”
Section: Modeling Methodsmentioning
confidence: 99%
“…Advantages and limitations of the analyzes and of the nondestructive methods are discussed based upon the information available in the scientific literature. An evaluation of the current criteria was performed in [28] using the minimum buckling strength calculation using a developed 3D nonlinear analysis model. The results show that the allowable additional compressive stress was reduced with a comparatively small lateral resistance.…”
Section: Review Of the Current Studiesmentioning
confidence: 99%
“…The analysis revealed that while the temperature gradient does affect the bridge support reactions, it does not have a significant impact on the stresses in CWRs or track stability. Yun et al [18] developed a three-dimensional TBI numerical model and carried out a nonlinear analysis to calculate the permissible additional compressive stresses by considering different track conditions. According to the obtained results, it was concluded that the prescribed permissible values of additional compressive stresses should be reduced tracks having relatively small lateral resistance.…”
Section: Introductionmentioning
confidence: 99%